Pearls of Meaning : Studies on Persian Art, Poetry, ..f.sm and History of Iranian Studies in Europe.J.T.P. de Bruijn - Bruijn, J. T. P. de (Iranian studies series (Leiden, Netherlands), 2020)
Pearls of Meanings offers a collection of essays by J.T.P. (Hans) de Bruijn, leading scholar in the field of Persian Studies, in which essential domains of Persian culture such as poetry and Sufism are analyzed in an exemplary fashion. While poetry plays a pivotal position in these essays, the reception of Persian literary tradition in Europe is another focus of the volume, thereby representing the studies of a generation of scholars such as A. Reland (1676-1718), C.H. Ethe (1844-1917), J.F. von Hammer-Purgstall (1774-1856) and E.G. Browne (1862-1926) who devoted their attention to Persian culture.